Translation and validation of the Chinese version of the Pancreatic Exocrine Insufficiency Questionnaire in patients after pancreatectomy - Huiping Yu; Wang Su; Lei Cui; Jianjian Wang; Kuirong Jiang; Xiaoping Fang (Medicine, 2026)
Pancreatic exocrine insufficiency (PEI) is common after pancreatic resection, but no Simplified Chinese PEI-specific patient-reported measure has undergone published cross-cultural evaluation. We translated and adapted the Pancreatic Exocrine Insufficiency Questionnaire (PEI-Q) and evaluated selected psychometric properties in patients after pancreatectomy. Following Beaton guidelines, the PEI-Q was translated and cross-culturally adapted. This single-center cross-sectional study included 163 patients. Item analysis, content validity assessment, principal component analysis, principal axis factoring sensitivity analysis, parallel analysis, and confirmatory factor analysis of the original 3-domain structure were performed. Internal consistency was evaluated; test–retest reliability, criterion validity, and responsiveness were not. Overall Cronbach alpha was 0.813 (95% confidence interval: 0.742–0.857); domain alphas were 0.667, 0.719, and 0.603, with 2 domains below 0.70. Total-scale McDonald omega was 0.820. Corrected item-total correlations ranged from −0.006 to 0.680; removing item 14 increased alpha to 0.843. Exploratory analyses retained 3 factors, but confirmatory factor analysis did not support the original structure (comparative fit index, 0.710; Tucker-Lewis index, 0.664; root mean square error of approximation, 0.130; standardized root mean square residual, 0.130). Principal axis factoring confirmed low communality for item 14 (0.013). The bowel movement symptoms domain showed a 25.8% floor effect; no ceiling effects occurred. The Chinese PEI-Q showed strong content validity and acceptable overall internal consistency. However, 2 domains had borderline consistency, and the original structure was not confirmed. It may support symptom monitoring and patient-clinician communication but should not be used for diagnosis or regarded as fully validated until further evaluation.